Hypnosis and Predictive Models of Consciousness - Gadotti, Erik; Casiglia, Edoardo (Advances in Social Sciences Research Journal, 2026)
This article aims to present a model to explain the phenomenology of hypnosis, with particular reference to plastic monoideism and its phenomenology, integrating some of the current scientific theories of consciousness, particularly those of Karl Friston’s free energy theory. Experimental studies demonstrate the existence of a close relationship between the individual’s representational system on the one hand, and their neurophysiological, endocrine, and immune systems on the other. In hypnosis, mental images immediately reverberate on the physical plane in such a profound way that they alter even the most primitive systems, such as vision and pain. It has been demonstrated that these processes occur when the mind focuses on a single idea, but why and how this occurs is unknown. At the same time, studies on consciousness have provided significant contributions to understanding the models we use to interact with reality and create our internal reality. Among the various theoretical approaches, those based on a constructivist epistemological paradigm would seem to be most in tune with the phenomenology of hypnosis. The theories of Anil Seth, Andy Clark, and Chris Frith (who share the idea that our brain is not a passive receiver of information but a predictive machine, that consciousness is a controlled hallucination, and that the mind extends to encompass social reality and artifacts) open the possibility of investigating the study of hypnosis. Within this line of thought, Karl Friston’s free energy theory proposes a mathematical-statistical theoretical model that extends these concepts to every living being, from cells to the human brain. This line of research has two important implications: 1) having a theoretical model that can be implemented through algorithms capable of explaining hypnotic phenomena paves the way for the use of technologies to support the clinical applications of hypnosis; 2) Having a tool like hypnosis that can be interpreted in light of the theory of consciousness opens the way to the possibility of studying consciousness using hypnosis.